Accuracy of non‐contrast quiescent‐interval single‐shot and quiescent‐interval single‐shot arterial spin‐labelled magnetic resonance angiography in assessment of peripheral arterial disease in a diabetic population. Issue 1 (10th February 2020) - Lam, Adrienne; Perchyonok, Yuliya; Ranatunga, Dinesh; Lukies, Matthew W; Richmond, Danielle; Hornsey, Emma K; McColl, Brenden; Heidrich, Jason; Ko, Pei‐Heng; Spelman, Tim; Chuen, Jason; Edelman, Robert R; et al.
Abstract: Introduction: Diabetic patients with peripheral arterial disease (PAD) are challenging to assess. Non‐contrast magnetic resonance angiography (MRA) offers a safe alternative in patients with renal impairment. The study objective is to evaluate accuracy of lower limb quiescent‐interval single‐shot (QISS) MRA and pedal QISS‐arterial spin‐labelled (ASL) MRA for detection of significant stenosis in diabetic patients with PAD. Methods: Combined QISS and QISS‐ASL MRA was performed in 32 diabetic PAD patients (20 male, 12 female; mean 69 years; 8 with critical ischaemia). Two readers assessed haemodynamically significant (>50%) stenosis and diagnostic confidence on MRA, against digital subtraction angiography (DSA) as the reference standard, with subgroup analysis of patients with severe renal impairment (n = 7). Inter‐reader agreement of stenosis and diagnostic confidence were evaluated. Test–retest reproducibility was evaluated in 10 subjects who underwent repeat MRA on a different day. Results: At DSA, 262/645 segments (40.6%) had haemodynamically significant stenoses. MRA accuracy was 78.1% (478/612) and 75.6% (464/614), sensitivity 64.7% (161/249) and 77.5% (193/249), and specificity 87.3% (317/363) and 74.2% (271/365) for 2 readers. MRA accuracy was 80.9% and 80.7% for readers 1 and 2, respectively, in patients with severe renal impairment. QISS MRA but not pedal QISS‐ASL MRA was considered of diagnostic image quality. Inter‐reader agreement was moderate for stenosis ( ĸ = 0.60) and diagnostic confidence ( ĸ = 0.41). Test–retest reproducibility was high ( ĸ = 0.87) and moderate ( ĸ = 0.54) for individual readers. Conclusions: Quiescent‐interval single‐shot MRA has reasonable accuracy in a diabetic PAD population with high burden of disease, providing a non‐contrast option in patients with renal impairment. QISS‐ASL MRA requires further optimisation to be clinically feasible.